Multivalued Fixed Point Results for New Generalized F-Dominated Contractive Mappings on Dislocated Metric Space with Application - Tahair Rasham (Journal of Function Spaces, 2018)
The purpose of this paper is to find out fixed point results for semi-α⁎-dominated multivalued mappings fulfilling a new generalized locally F-dominated multivalued contractive condition on a closed ball in complete dislocated metric space. Example and application both are given to show the novelty of our results. Our results merge, extend, and infer many results.